Prenatal substance exposure and child maltreatment: a systematic review - Austin, Anna E. (Child maltreatment, 2022)
State and federal policies regarding substance use in pregnancy, specifically whether a notification to child protective services is required, continue to evolve. To inform practice, policy, and future research, we sought to synthesize and critically evaluate the existing literature regarding the association of prenatal substance exposure with child maltreatment. We conducted a comprehensive electronic search of PubMed, Web of Science, PsycInfo, CHINAL, Social Work Abstracts, Sociological Abstracts, and Social Services Abstracts. We identified 30 studies that examined the association of exposure to any/multiple substances, cocaine, alcohol, opioids, marijuana, and amphetamine/methamphetamine with child maltreatment. Overall, results indicated that substance exposed infants have an increased likelihood of child protective services involvement, maternal self-reported risk of maltreatment behaviors, hospitalizations and clinic visits for suspected maltreatment, and adolescent retrospective self-report of maltreatment compared to unexposed infants. While study results suggest an association of prenatal substance exposure with child maltreatment, there are several methodological considerations that have implications for results and interpretation, including definitions of prenatal substance exposure and maltreatment, study populations used, and potential unmeasured confounding. As each may bias study results, careful interpretation and further research are warranted to appropriately inform programs and policy.